PENGENAAN SANKSI ADMINISTRATIF PELANGGARAN INTENSITAS PEMANFAATAN RUANG - Abitya Indah Rosiani; Rusdianto Sesung (Jurnal HUKUM BISNIS, 2023)
Spatial use control is carried out to realize spatial use in accordance with the spatial plan and implemented to encourage everyone to comply with the established spatial plan, utilize space in accordance with the spatial plan, and comply with the provisions stipulated in the requirements for space utilization activities. One of the ways to control the use of space is through the imposition of sanctions. This study aims to provide a description and academic recommendations for setting administrative fines for violations of the intensity of spatial use in the context of building construction in the city of Surabaya. This study tries to discuss the forms of violations of spatial use intensity and legal conformity in the imposition of administrative sanctions for violations of spatial use intensity against the construction of buildings in the city of Surabaya. The conclusion of this study is that the form of violation of the intensity of spatial use is a violation of the technical provisions as stated in the Description of the City Plan (KRK) which is the basis for preparing the building's technical plan, while the legal conformity is carried out when applying for a Building Permit and determined by a Regional Fines Decree (SKDD) ) with the amount of the administrative fine taking into account certain aspects. To apply fines for violating the intensity of spatial use, the Surabaya City Government needs to compile a legal basis regarding the procedures for imposing fines for violating the intensity of spatial use.Keywords: spatial use control, administrative sanctions.